Multiculturalism and tolerance: challenges of the modern world (Journal of Philosophy Culture and Political Science, 2018)
Modern world trend is worsening ethnic confl icts, the growth of intolerance, even in countries that haveachieved a high quality of life. It comes amid a global economic crisis and the rise of migration fl ows. All thiscauses the relevance and importance of scientifi c and philosophical discourse on rethinking the role, importanceand prospects of multiculturalism in the context of the challenges and imperatives of a globalizing world..Key words: multiculturalism, tolerance, identity, globalization, dialogue of cultures.